Impact Of Covid-19 On The Linkages Between Indochina Metal Futures Markets (Journal of Pharmaceutical Negative Results, 2022)
This paper attempts to test whether the Covid-19 pandemic has an impact on the linkages of the metal futures market of India andChina. Taking Daily closing prices from 4 Jun 2016 to 23 Apr 2021 for the seven metals, including copper, aluminum, zinc, lead,nickel, gold, and silver, have been included in the study in the pre-announcement and post-announcement of covid-19 as a pandemic.The autoregressive distributed lag (ARDL) bound test and Johansen cointegration test report no cointegrating relationship between themarkets for all the metal futures before the covid period. There is no change in the absence of cointegration in the post-announcementperiod of Covid-19. Similarly, Granger causality results report no change in the short-run relationship between the metal futures marketsexcept for silver futures. The results have implications for portfolio managers and investors looking to reshuffle their portfolios in thelight of changes in the market due to the covid-19 pandemic.